The Launch of JUCMD - Shahid Mahmud Malik (University of Lahore, 2022)
I have been asked by my editorial team to write a small note for the first issue of this journal entitled, JUCMD (Journal of University College of Medicine and Dentistry). Reflecting on what makes a good journal great reminds of the sayings of Dr Bartosz Hudzik, a young cardiologist at a medical university in Poland.  First and foremost, there is the team of dedicated and highly qualified editors who provide valuable guidance on the journal contents. In addition, there are manuscript authors, equally important as the editors, as they are the ones conducting research, writing and rewriting drafts, and submitting the manuscript in hopes that it will be published. Then, there are the reviewers, who advise the editors on the importance and novelty of the findings and the soundness of the research methodology. Finally, there are the readers, who look to the journal for accurate and up-to-date scientific and clinical information. We have this exact recipe right at the start of our journal in the form of a very active and energetic editorial board and a competent pool of reviewers.